Use of ionic liquids in SIMS depth profiling. (12th September 2014) - Nakata, Yoshihiko; Fujiyama, Noriyuki; Sameshima, Junichiro; Yoshikawa, Masanobu; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; Hong, Tae Eun
<x xml:space="preserve">Abstract</x> A room temperature ionic liquid (IL) is a molten salt with melting point below 100 °C and has extremely low vapor pressure, allowing use in a high vacuum chamber. In scanning electron microscopy, the ILs have been found to behave as electrically conductive materials and successfully applied for conductive coating of insulating specimens. It is well known that dynamic SIMS analysis of an insulator causes charge buildup and requires a conductive film coating and electron gun, which can distort depth profiling of metal elements. In this study, 1‐ethyl‐3‐methylimidazolium tetrafluoroborate was employed to test the applicability for charge neutralization in depth profiling of insulators. Mass spectra were successfully obtained from the IL droplets deposited onto a Si substrate without charge buildup. Deposition of the IL onto fiber pulp samples enabled us to acquire continuous secondary ions from the pulp samples. It implies the potential use of the IL as a conductive film for depth profiling of metal elements in insulators such as SiO2 and SiN. Copyright © 2014 John Wiley & Sons, Ltd.